Heparin Bridging Therapy for Patients on Chronic Oral Anticoagulants in Periprocedural Settings - Nikolakopoulos, Ilias; Spyropoulos, Alex C. (Seminars in Thrombosis and Hemostasis, 2020)
Interruption of chronic anticoagulation due to the bleeding risk associated with an elective procedure may also lead to an elevated risk of thromboembolism. Periprocedural bridging with either unfractionated heparin or low-molecular weight heparin had been the mainstay of therapy for many patients receiving chronic warfarin treatment based on an estimation of a patient's thromboembolic risk. However, recent results from cohort studies and placebo-controlled randomized trials in the periprocedural use of heparin bridging for warfarin-treated patients reveal a consistent two- to three-fold increase in the risk of major bleeding and no benefit in terms of a reduction in the risk of stroke and systemic embolism. The most recent antithrombotic guidance statements suggest that the majority of patients on chronic warfarin, except those at high risk of thromboembolism, may safely interrupt and resume warfarin without heparin bridging in elective periprocedural settings. In addition, data from the use of heparin bridging in patients on direct oral anticoagulants during temporary interruption for an elective procedure also reveal harm and no benefits of this approach. A strategy that considers the pharmacokinetic properties of the direct oral anticoagulants, the bleeding risk of each procedure, and patient renal function would safely obviate the need for heparin bridging. In this review, the authors summarize the major studies of heparin bridging for patients on chronic oral anticoagulants that may lead to a change in practice in periprocedural antithrombotic management and define an evidence-based heparin bridging protocol for those patient groups who may be the candidates for this approach.
Keywords: perioperative; bridging; heparin; warfarin; direct oral anticoagulants